Perbedaan Stres Akademik Mahasiswa Berdasarkan Jenis Kelamin - Dony Darma Sagita; Shafna Utami Nur Fairuz; Syifa Aisyah (STKIP Andi Matappa, 2021)
Stress is a complex problem that occurs in individuals in their lives. This study aims to find differences in student academic stress based on gender. This study uses a comparative descriptive research method by using Non Probability Sampling, with the convenience sampling technique. The data analysis technique was used the T-Test combined with the RASCH stacking model. The results showed that there was no significant difference in academic stress between men and women.